Dépistage de l’hypothyroïdie congénitale à l’hôpital de la Mère et de l’Enfant Lagune de Cotonou - Houndetoungan, Gilles David; AMOUSSOU-GUENOU, KUASSI MARCELLIN; ALAO, Maroufou Jules; Fachinan, Olatounde Herbert (My University, 2012)
Congenital hypothyroidism is a preventable cause of mental retardation in children. Systematically detected and treated in Western countries, this condition remains neglected in Africa. This study was conducted from March through July 2011 in the Gynecology-Obstetrics Department and the Paediatrics Department of Hôpital de la Mère et de l’Enfant Lagune (HOMEL) and in the Radioimmunoassays laboratory (SeRiD) of Cotonou. Authors’ objective was to screen newborns for congenital hypothyroidism. Five hundred and forty-nine newborns were enrolled in the study and 35 (6.4%) had abnormal levels of thyroid markers in the first assay on umbilical cord blood. Controls that were performed in 27 children between the third and 15th days disclosed no abnormality. Maternal fever and birth asphyxia appeared to influence hyperthyrotropinemia while low birth weight, birth asphyxia and non-cephalic presentations were associated with hypothyroxinemia.
Keywords: Hypothyroïdie congénitale; Dépistage; Marqueurs thyroïdiens; Radio-analyse